Loss of Ambra1 promotes melanoma growth and invasion - Luca Di Leo; Valérie Bodemeyer; Francesca M. Bosisio; Giuseppina Claps; Marco Carretta; Salvatore Rizza; Fiorella Faienza; Alex Frias; Shawez Khan; Matteo Bordi; Maria P. Pacheco; Julie Di Martino; et al. (Nature Communications, 2021)
The absence of scaffold protein Ambra1 leads to hyperproliferation and growth in mouse models. Here the authors show that Ambra1 deficiency accelerates melanoma growth and increases metastasis in mouse models of melanoma through FAK1 hyperactivation.